Penggunaan Software Geogebra Classic Pada Mata Pelajaran Matematika (Program Linear) - Nurbaeti Nurbaeti; Akhmad Syahid (Universitas Muslim Indonesia, 2023)
Geogebra classic as it is known today can be run through various platforms. At the beginning of the introduction and development of GeoGebra, I learned about the Makassar City Mathematics MGMP training being held by the Directorate General of the Republic of Indonesia in South Sulawesi in 2021. At that time, Geogebra Classic was only introduced as a free mathematics software that could be run via the Windows operating system. In its development, GeoGebra Classic has undergone many changes, especially now that it can be used on various platforms. At the beginning of its development, GeoGebra Classic was only used for two-dimensional geometry and algebra material. But now, GeoGebra Classic can be used for three-dimensional geometry with other capabilities. Geogebra classic that is used today is geogebra classic. Geogebra classic was originally known as geogebra 5, then geogebra 6. At the time this article was written, it was known as geogebra classic. At present, the compression of computer programs in learning mathematics is a necessity and is a mandatory requirement for students at both the elementary, secondary, and tertiary levels today. There are lots of computer programs and Android phones that can be used in learning mathematics, including the GeoGebra application. Geogebra classic is a dynamic program with a variety of facilities that are very useful for students, especially on the subject of linear programming, and can be used as a medium for learning mathematics. In addition, Geogebra classic can be used to demonstrate or visualize mathematical concepts as well as tools to construct these concepts. With this program, abstract mathematical objects can be visualized and manipulated quickly and efficiently.